Expression of Recombinant Human Alpha-Lactalbumin in the Milk of Transgenic Goats Using a Hybrid Pomoter/Enhancer. (9th January 2014) - Yuan, Yu-Guo; An, Liyou; Yu, Baoli; Song, Shaozheng; Zhou, Feng; Zhang, Liqing; Gu, Yinyin; Yu, Minghui; Cheng, Yong
Abstract : To improve nutrient content of goat milk, we describe the construction of a vector (pBLAC) containing a hybrid goat β -lactoglobulin (BLG) promoter/cytomegalovirus (CMV) enhancer. We also describe the generation of transgenic goats expressing rhLA by somatic cell nuclear transfer (SCNT). Of 334 one-cell stage embryos derived from three transgenic cell lines and 99 embryos derived from non-transgenic (NT) cells surgically transferred to the oviducts of 37 recipients, two recipients delivered two kids (2%) from the non-transfected line and five recipients delivered six kids (1.8%) from transgenic cell lines, three of which died within 2 days. Compared to the NT donor cells, transfection of donor cells does not negatively affect the development of nuclear transfer embryos into viable transgenic offspring. However, the clone efficiency in cell line number 1 was lower than that in numbers 2 and 3, and in the NT lines (0.9% versus 1.9% 2.4% and 2%; P < 0.05 ). Two transgenic cloned goats expressed rhLA in the milk at 0.1–0.9 mg/mL. The mammary gland-specific expression vector pBLAC with hybrid BLG/CMV can drive the hLA gene to express in vitro and in vivo . These data establish the basis for use of a hybrid promoter/enhancer strategy to produce rhLA transgenic goats.